Challenges and Perspectives for NASICON‐Type Electrode Materials for Advanced Sodium‐Ion Batteries. Issue 48 (19th June 2017) - Chen, Shuangqiang; Wu, Chao; Shen, Laifa; Zhu, Changbao; Huang, Yuanye; Xi, Kai; Maier, Joachim; Yu, Yan
Abstract: Sodium‐ion batteries (SIBs) have attracted increasing attention in the past decades, because of high overall abundance of precursors, their even geographical distribution, and low cost. Apart from inherent thermodynamic disadvantages, SIBs have to overcome multiple kinetic problems, such as fast capacity decay, low rate capacities and low Coulombic efficiencies. A special case is sodium super ion conductor (NASICON)‐based electrode materials as they exhibit – besides pronounced structural stability – exceptionally high ion conductivity, rendering them most promising for sodium storage. Owing to the limiting, comparatively low electronic conductivity, nano‐structuring is a prerequisite for achieving satisfactory rate‐capability. In this review, we analyze advantages and disadvantages of NASICON‐type electrode materials and highlight electrode structure design principles for obtaining the desired electrochemical performance. Moreover, we give an overview of recent approaches to enhance electrical conductivity and structural stability of cathode and anode materials based on NASICON structure. We believe that this review provides a pertinent insight into relevant design principles and inspires further research in this respect. Abstract : Sodium super ion conductor (NASICON)‐based electrode materials, exhibiting pronounced structural stability and exceptionally high ion conductivity are promising materials for sodium storage. Challenges and perspectives of NASICON‐type electrode materials are discussed, and electrode structure design principles for obtaining the desired electrochemical performance are highlighted. Recent progress in enhancing electrical conductivity and structural stability of NASICON materials is summarized.